Comparison of total body vitamin A stores using individual versus population 13C-natural abundance of serum retinol in preschool children and women residing in 6 diverse African countries - Gannon, Bryan M.; Sombié, Olivier O.; Zeba, Augustin N.; Nama, Gabriel Medoua; Bekele, Tesfaye Hailu; Woldeyohannes, Meseret; van Stuijvenberg, Martha E.; Dhansay, Muhammad A.; Urio, Elisaphinate M.; Kaliwile, Chisela; Chileshe, Justin; Kalungwana, Ng’Andwe; et al. (Elsevier, 2023)
Background Stable isotope techniques using 13C to assess vitamin A (VA) dietary sources, absorption, and total body VA stores (TBSs) require determination of baseline 13C abundance. 13C-natural abundance is approximately 1.1% total carbon, but varies with foods consumed, supplements taken, and food fortification with synthetic retinyl palmitate.